The role of 18F-FDG PET/CT in patients with serous cavity effusion of undetermined origin: a retrospective clinical study - Xianwen Hu; Ya Li; Jiong Cai; Pan Wang (PeerJ)
Aim The diagnostic performance of positron emission tomography with fluoro-18 fluorodeoxyglucose integrated with computed tomography (18F-FDG PET/CT) in identifying the primary cause of unknown serous effusion and malignant tumors with serous metastasis was evaluated in our study. Methods A retrospective analysis was conducted on 134 patients with unexplained serous cavity effusion, including pericardial effusion, pleural effusion, and ascites, who underwent 18F-FDG PET/CT scans. The cohort comprised 94 cases of malignant disease and 40 cases of benign disease. Visual analysis of all 18F-FDG PET/CT images and semi-quantitative analysis by measuring maximum standardized uptake value (SUVmax) in the region of interest were performed. The diagnostic capabilities of SUVmax, Ca125, Ca199, and serum carcinoembryonic antigen were compared by plotting the areas under the receiver operating characteristic curve. Results The primary disease of serous cavity effusion was diagnosed with a sensitivity of 90.1%, specificity of 78.8%, and accuracy of 85.7% using 18F-FDG PET/CT. The SUVmax of primary malignant lesions was found to be significantly higher than that of benign lesions, with values of 12.83 ± 6.64 and 4.48 ± 3.16 (P < 0.001), respectively. The detection of serous cavity metastasis by PET/CT showed a sensitivity of 84.3%, specificity of 94.0%, and accuracy of 88.3%. In receiver operating characteristic (ROC) analysis, the area under the curve of SUVmax was the largest (P < 0.01), significantly surpassing that of serum Ca125, Ca199, and CEA. Conclusion 18F-FDG PET/CT was determined to be an effective imaging modality for detecting undetermined serous cavity effusion, exhibiting high diagnostic performance in the differentiation of primary disease from benign to malignant and the evaluation of serous cavity metastasis.